Rheology of double (w/o/w) emulsions prepared with soybean milk and fortified with calcium - Márquez, Andrés Leonardo (2010)
The objective of this work was to study the rheological behavior of water-in-oil-in-water (w/o/w) emulsions prepared with soybean milk and sunflower oil, with different calcium solutions as the internal aqueous phase, in order to evaluate them as a vegetable substitute of whipped dairy cream. The obtained systems exhibited a creamy texture, which was attributed to the swelling of w/o droplets because of the osmotic gradient generated by the inclusion of soluble salts in the internal aqueous phase. A secondary factor could be the flocculation of w/o droplets due to the interaction of released calcium with soybean proteins at the interface. Consequently, the increase of calcium chloride content produced emulsions with higher consistency. A pasteurization produced flocculation and coalescence of w/o droplets only at high calcium chloride content. These double emulsions could be a potential alternative to the whipped dairy cream, because of their texture, reduced fat content and calcium contribution.